2016
DOI: 10.1177/0270467617726221
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Evaluating Mobile Device Adoption in Community Sports Organizations

Abstract: Few studies have been conducted into the use of mobile technologies at community-based organizations. Community sport organizations (CSOs) typically operate within a defined geographic area and rely on the primary support of volunteers. Based on the characteristics of mobile-based information services, this article proposes a model that provides a guide for CSOs to classify mobile applications through four mobile utility factors and three innovation adoption determinants (cost, skill requirements, and compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
3
9
0
Order By: Relevance
“…The study results showed negative and significant effects of using social networks at the workplace on the job inattention of employees of Sport and Youth Department of Golestan Province. This result was consistent with the findings of Makvand & Fernandez and Moqbel & Kock [24,34]. This result means that more use of social networks by employees of the Golestan Province Sports and Youth Department results in more job inattention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study results showed negative and significant effects of using social networks at the workplace on the job inattention of employees of Sport and Youth Department of Golestan Province. This result was consistent with the findings of Makvand & Fernandez and Moqbel & Kock [24,34]. This result means that more use of social networks by employees of the Golestan Province Sports and Youth Department results in more job inattention.…”
Section: Discussionsupporting
confidence: 91%
“…The study by Taylor et al, on British organizations showed that using social networks in organizations was a tool to bother employees, and the lack of specific rules in this area increased its intensity [33]. Makvand & Fernandez in a study entitled "The Impact of Social Networking on Organizational Behaviors in Non-Democratic Countries" found that the employment of these networks led to the job inattention, lack of time management, reduced participatory behaviors, and reduced group work [34] Holland et al, found that the employment of social networks at workplace led employees to devote more time to using such networks and the use of these networks was more common among younger employees than older employees [35]. Chung & Kim found that the employment of social networks in organizations led to increased ostracism.…”
Section: Introductionmentioning
confidence: 99%
“…However, the currently available data does not enable me to determine whether this is the case here. That that some boxing clubs and coaches only used digital tools for necessary communications (e.g., to post that the boxing gym was closed due to the COVID-19 pandemic) could also be interpreted as a form of resistance to digitalization in sport, as explored in a few previous studies (Trabal, 2008;Sellitto et al, 2016;Tjønndal, 2020). As Trabal (2008) found, coaches are more likely to resist technological innovation than athletes.…”
Section: Discussionmentioning
confidence: 99%
“…As Trabal ( 2008 ) found, coaches are more likely to resist technological innovation than athletes. Sellitto et al ( 2016 ) argue that many sports organizations do not use digital tools because they do not have the expertise to exploit them productively. This may also be the case for the boxing clubs and coaches making limited use of digital tools and online training strategies during the shutdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation